Analysis and Design of Piled Raft Foundation Taking into Account Interaction Factors - Irfan Jamil; Irshad Ahmad; Shahid Ali Khan; Wali Ullah; Maaz Amjad; Beenish Jehan Khan; Hassan Nasir (Advances in Civil Engineering)
In a combined piled raft foundation (CPRF) both raft and piles take their share of the total load applied. However, in practice, the contribution of a raft in taking load is usually ignored and the load is assumed to be supported on piles. This way of CPRF becomes excessively conservative and uneconomical. To economize the design, relative load sharing of raft and piles in CPRF has to be found. In this connection, different simplified methods have been developed, each one with some limitations. In this study, three simplified methods have been applied to two cases of pile-raft systems. The methods include Randolph, Poulos-Davis-Randolph, and modified Poulos-Davis-Randolph. The first case is a hypothetical case consisting of a 12 m × 12 m raft supported on a square group of nine piles. The second case study is an actual eight-story building to be constructed in Peshawar, Pakistan. The building is supported on a pile-raft system, with raft resting on very soft clay underlain by dense sand. The two case studies are also modelled in the finite element program PLAXIS 3D for comparison. The results of all the simplified methods are comparable with PLAXIS 3D. However, the Randolph method is much closer to PLAXIS 3D for the two cases studied. Furthermore, it is also shown that piles in a piled raft system can be used as “stress reducers” as well as a “settlement reducers.” Additionally, the effect of interaction factors is also evaluated with the s/d ratio as well as with varying soil stiffness. It was concluded that ignoring these factors leads to a very unsafe design of the pile-raft system.